Scopes and Limitations of Albert Schweitzer's Ethical System - Zagorac, Ivana (Array, 2011)
First part of the presentation focuses on the main characteristics of Albert Schweitzer's ethical system: he defines his ethics as rational, absolute, universal, and of a great spiritual significance. Implications of such characteristics are multilayered although coherent within the framework of 'reverence for life' principle until the moment of their confrontation with Schweitzer's demand for necessity of practical realization. His ‘living ethics’ is challenged by practical value conflicts which could be resolved only by the abolition of the highest principle itself. Schweitzer notices this tension and tries to overcome it by offering different solutions which will be analyzed in the second part of the presentation. Finally, having in mind the high value of his ‘reverence for life’ principle in modern bioethics, in the concluding part we will examine Schweitzer’s success in resolving weak points of his own ethical system.